LESSON 3 THE LIMIT OF A FUNCTION 3x 3 6 x 2 5 x 10 Example Consider the function f ( x ) . x2 The domain of f is the set of all real numbers except for 2. What is the value of f when x is close to 2? x 2.5 2.1 2.01 2.001 2.0001 2.00001 2.000001 2.0000001 2.00000001 2.000000001 2.0000000001 2.00000000001 2.000000000001 f(x) 13.75 8.23 7.1203 7.012003 7.00120003 7.0001200003 7.000012000003 7.00000120000003 7.0000001200000003 7.000000012000000003 7.00000000120000000003 7.0000000001200000000003 7.000000000012000000000003 3 ( 2.001) 3 6 ( 2.001) 2 5 ( 2.001) 10 NOTE: f ( 2.001) = 2.001 2 3 (8.012006001) 6 ( 4.004001) 10.005 10 = 0.001 24.036018003 24.024006 10.005 10 0.007012003 = = 7.012003 0.001 0.001 3x 3 6 x 2 5 x 10 It appears that as x is getting closer to 2, f ( x ) is getting x2 closer to 7. We let x get closer to 2 through values that are larger than 2. What about values of x which are smaller than 2? Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 x 1.5 1.9 1.99 1.999 1.9999 1.99999 1.999999 1.9999999 1.99999999 1.999999999 1.9999999999 1.99999999999 1.999999999999 f(x) 1.75 5.83 6.8803 6.988003 6.99880003 6.9998800003 6.999988000003 6.99999880000003 6.9999998800000003 6.999999988000000003 6.99999999880000000003 6.9999999998800000000003 6.999999999988000000000003 3 (1.99 ) 3 6 (1.99 ) 2 5 (1.99 ) 10 NOTE: f (1.99 ) = 1.99 2 3 (7.880599 ) 6 ( 3.9601 ) 9.95 10 23.641797 23.7606 9.95 10 = 0.01 0.01 0.068803 = 6.8803 0.01 3x 3 6 x 2 5 x 10 Again, it appears that as x is getting closer to 2, f ( x ) x2 getting closer to 7. is 3x 3 6 x 2 5 x 10 Does the rational expression simplify? It will simplify if x2 x 2 is a factor of 3x 3 6 x 2 5x 10 . You might try factoring 3x 3 6 x 2 5x 10 by grouping together the first two terms, which have a 3x 2 in common, and the last two terms, which have a 5 in common. 3x 3 6 x 2 5x 10 = 3x 2 ( x 2 ) 5 ( x 2 ) = ( x 2 ) ( 3x 2 5 ) Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 NOTE: We obtained the final factorization (product) by factoring out the common x 2 factor in the expression 3x 2 ( x 2 ) and in the expression 5 ( x 2 ) . 3x 3 6 x 2 5 x 10 ( x 2 ) ( 3x 2 5 ) Thus, = = 3x 2 5 for all x such that x2 x2 x 2. 3x 3 6 x 2 5 x 10 What does the graph of f ( x ) look like? It is the graph of x2 y 3x 2 5 with the point ( 2 , 7 ) removed. This graph was created using Maple. Notation: The mathematical expression x a means “x approaches a”. Thus, f ( x ) L means “ f ( x ) approaches L”. For the example above, we may write the statement: As x 2 , f ( x ) 7 . We are going to define this statement as a limit using the following definitions. Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 Informal Definition of a Limit: To say that the limit of f ( x ) is L as x f ( x ) L , means that f ( x ) gets closer and closer approaches a , denoted by xlim a to L (that is, f ( x ) approaches L) as x gets closer and closer to a (that is, x approaches a). f ( x ) L means “As x a , f ( x ) L .” That is, xlim a 3x 3 6 x 2 5 x 10 7 in the example above, then Since as x 2 , f ( x ) x2 3x 3 6 x 2 5 x 10 7. f ( x ) 7 or xlim we may write xlim 2 2 x2 Formal Definition of a Limit: To say that the limit of f ( x ) is L as x approaches f ( x ) L , means given any 0 , there exists a 0 such a , denoted by xlim a that f ( x ) L whenever 0 x a . NOTE: That condition that x a 0 in the definition above means that x a . NOTE: The expression f ( x ) L is the distance between f ( x ) and L on the real number line and the expression x a is the distance between x and a on the real number line. Thus, the condition that f ( x ) L whenever 0 x a is saying that whenever the distance between x and a is less than and x a , then the distance between f ( x ) and L is less than . NOTE: The inequality f ( x ) L is equivalent to the inequality f ( x ) L and this inequality is equivalent to the inequality L f ( x ) L . This last inequality says that f ( x ) is in the interval (L , L ). L L L Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 x a is equivalent to the inequality Similarly, the inequality a x a . This inequality says that x is in the interval ( a , a ) . Thus, the inequality 0 x a is equivalent to saying that a x a and x a . This says that x is in the set (a , a) (a, a ) a a a f ( x) f (a) . Sometimes, xlim a Examples Find the following limits if they exist. 1. lim ( 3x 5 ) x 1 lim ( 3x 5 ) 3 5 8 x 1 ( 3x 5 ) 8 , this means that as x is getting Since we are saying that xlim 1 closer to 1 ( x 1 ), 3 x 5 is getting closer to 8 ( 3 x 5 8 ). Let’s see if this is true. Let f ( x ) 3 x 5 . f (1.1) 3 (1.1) 5 3.3 5 8.3 f (1.01) 3 (1.01) 5 3.03 5 8.03 f (1.001) 3 (1.001) 5 3.003 5 8.003 f (1.0001) 3 (1.0001) 5 3.0003 5 8.0003 f ( 0.9 ) 3 ( 0.9 ) 5 2.7 5 7.7 f ( 0.99 ) 3 ( 0.99 ) 5 2.97 5 7.97 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 f ( 0.99 9) 3 ( 0.999 ) 5 2.997 5 7.997 f ( 0.99 99) 3 ( 0.9999 ) 5 2.9997 5 7.9997 ( 3x 5 ) 8 using the formal definition of limit, we need To show that xlim 1 to show that for any 0 , there exists a 0 such that 3x 5 8 whenever 0 x 1 . Since 3x 5 8 = 3x 3 = 3 x 1 , then 3x 5 8 whenever 0 3 x 1 , which implies that 3x 5 8 whenever 0 x 1 choose . 3 3 . Thus, given any 0 , Answer: 8 2. lim ( 8 x 2 x 4 ) x2 lim ( 8 x 2 x 4 ) 32 2 4 38 x2 ( 8 x 2 x 4 ) 38 , this means that as x is Since we are saying that x lim 2 2 getting closer to 2 ( x 2 ), 8x x 4 is getting closer to 38 2 ( 8x x 4 38 ). Check it out to see if this is true. ( 8 x 2 x 4 ) 38 using the formal definition of limit, To show that x lim 2 we need to show that for any 0 , there exists a 0 such that 8 x 2 x 4 38 whenever 0 x 2 . 2 2 NOTE: 8x x 4 38 = 8x x 34 = ( x 2 ) ( 8 x 17 ) Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 Since we are approaching 2 in a limiting sense, we could restrict ourselves to the interval described by the inequality x 2 1. This inequality is equivalent to the inequality 3 x 1 . Thus, if 3 x 1 , then 24 8 x 8 and 41 8 x 17 25 . Since 41 8 x 17 25 , 2 then 25 8x 17 41 . Since 8x x 4 38 = ( x 2 ) ( 8 x 17 ) 2 from above, then 8 x x 4 38 = ( x 2 ) ( 8x 17 ) = x 2 8x 17 < 41 x 2 . Thus, 8 x 2 x 4 38 whenever 41 x 2 , which implies that x2 8 x 2 x 4 38 whenever . Thus, given any 0 , choose min 1, 41 41 Answer: 38 3. h 2 4h 3 lim h 0 6h 2 h 9 h 2 4h 3 003 3 1 lim h 0 6h 2 h 9 009 9 3 h 2 4h 3 1 lim Since we are saying that h 0 2 , this means that as h 0 , 3 6h h 9 h 2 4h 3 1 2 3 6h h 9 Answer: 4. 1 3 lim 8 x4 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 lim 8 8 x4 NOTE: The limit of a constant is that constant. Answer: 8 5. 3x 3 6 x 2 5 x 10 lim x2 x2 3x 3 6 x 2 5 x 10 24 24 10 10 0 lim x2 x2 22 0 0 is called an indeterminate form because you can not determine 0 any information from it. NOTE: We saw in the example at the beginning of this lesson that 3x 3 6 x 2 5x 10 can be factored by grouping and we obtained that 3x 3 6 x 2 5x 10 = ( x 2 ) ( 3x 2 5 ) . Thus, we have that 3x 3 6 x 2 5 x 10 ( x 2 ) ( 3x 2 5 ) lim lim lim ( 3x 2 5 ) = 7 = = x2 x2 x2 x2 x2 Answer: 7 6. t 2 25 lim t5 t 5 t 2 25 25 25 0 lim Indeterminate Form t 5 t 5 55 0 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 (t 5)(t 5) t 2 25 lim lim ( t 5) 10 = t5 = tlim t5 t 5 5 t 5 Answer: 10 7. lim w lim w lim w 2 3 2 3 2 3 3w 2 4 9w 2 3w 2 22 0 Indeterminate Form 44 0 4 9w 2 3w 2 3w 2 1 1 1 lim lim 22 4 4 9w 2 = w 2 ( 2 3w) ( 2 3w ) = w 2 2 3w 3 3 ab 1 , then you can cancel the 3w 2 and 2 3w as NOTE: Since ba long as you provide a negative one in either the numerator or the denominator. For this problem, it easier to supply 1 in the numerator. Answer: 8. 1 4 x 2 5 x 24 lim x 3 4 x 2 7 x 15 x 2 5 x 24 9 15 24 0 lim Indeterminate Form x 3 4 x 2 7 x 15 36 21 15 0 We can make use of a theorem from algebra called the Factor Theorem. Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 Factor Theorem If p is a polynomial in variable x and p ( r ) 0 , then x r is a factor of the polynomial p. 2 2 Thus, x 3 is a factor of x 5 x 24 and 4 x 7 x 15 . 2 Thus, x 5 x 24 = ( x 3 ) ( x 8 ) and 4 x 2 7 x 15 = ( x 3 ) ( 4 x 5 ) ( x 3) ( x 8) x8 11 x 2 5 x 24 lim lim Thus, xlim = = x 3 ( x 3) ( 4x 5 ) x 3 4x 5 3 4 x 2 7 x 15 17 Answer: 9. 11 17 3r 2 14r 8 lim r 4 r 2 4r 32 3r 2 14r 8 48 56 8 0 lim Indeterminate Form r 4 r 2 4r 32 16 16 32 0 By the Factor Theorem given above, r ( 4 ) r 4 is a factor of 3r 2 14r 8 and r 2 4r 32 . Thus, ( r 4 ) ( 3r 2 ) 3r 2 10 5 3r 2 14r 8 lim lim lim = r 4 ( r 4 ) ( r 8 ) = r 4 r 8 12 6 r 4 r 2 4r 32 Answer: 5 6 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 10. 8t 2 22t 21 lim 3 12t 2 t 6 t 4 9 33 42 8t 22t 21 2 2 2 0 lim 2 Indeterminate Form 3 12t t 6 9 3 24 0 t 4 4 4 4 2 3 2 is a factor of 8t 22t 21 4 2 and 12t t 6 . This is equivalent to 4t 3 being a factor of 8t 2 22t 21 and 12t 2 t 6 . Thus, By the Factor Theorem given above, t 8t 2 22t 21 ( 4t 3 ) ( 2t 7 ) 2t 7 lim lim lim = 3 12t 2 t 6 3 ( 4t 3 ) ( 3t 2 ) = 3 3t 2 = t t t 4 4 4 3 7 6 28 34 2 = 9 8 = 17 2 9 2 4 Answer: 2 11. 24 x 2 4 x 3 lim x 6 x 2 12 x 36 2 3 In order to evaluate 24 x 4 x for x 6 , it is easier to use the factorization 2 3 2 3 2 for 24 x 4 x since 24 x 4 x = 4 x ( 6 x ) . Since the factor 6 x is 2 3 equal to zero when x 6 , then 24 x 4 x = 0 when x 6 . Thus, 24 x 2 4 x 3 0 0 lim 2 Indeterminate Form x 6 x 12 x 36 36 72 36 0 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 24 x 2 4 x 3 4x 2 ( 6 x ) lim = xlim x 6 x 2 12 x 36 6 ( x 6 )2 We can cancel the factor of 6 x in the numerator with one on the two factors of x 6 in the denominator as long as we supply a 1 in either the numerator or the denominator. Thus, we have that 4x 2 ( 6 x ) 4 x 2 ( 1) 144 lim = xlim = x6 6 x6 ( x 6 )2 0 Now, we need to make use of the following theorem, which will be proved at the end of this lesson. f ( x) lim lim f ( x ) 0 lim g ( x ) 0 Theorem If x a and x a , then x a g ( x ) does not exist (DNE). Using this theorem, we have that 24 x 2 4 x 3 4x 2 ( 6 x ) 4 x 2 ( 1) 144 lim DNE = xlim = xlim = x 6 x 2 12 x 36 6 6 x6 ( x 6 )2 0 Answer: DNE 12. lim 3w 67 7 w6 lim 3w 67 7 w6 w6 w6 18 67 7 66 49 7 0 0 0 The only available algebra step to try to simplify the fraction is to rationalize the numerator of the fraction. Thus, we have that Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 lim w6 3w 67 49 lim w6 lim ( w 6 ) ( 3w 67 7 ) h2 Answer: 3w 67 7 3w 67 7 = 3w 18 ( w 6 ) ( 3w 67 7 ) = wlim 6 ( w 6 ) ( 3w 67 7 ) 3 14 13. = wlim 6 3( w 6 ) w6 lim 3w 67 7 w6 3w 67 7 = wlim 6 w6 3 = 3 = 3w 67 7 49 7 = 3 14 5 8h 11 h2 Just like in the previous example, we will need to rationalize the numerator. Thus, lim h2 lim h2 lim h2 lim h2 5 8h 11 h2 5 8h 11 = hlim 2 h2 5 ( 8h 11) ( h 2)( 5 8h 11 ) = hlim 2 8h 11 ) = hlim 2 16 8h ( h 2)( 5 8 8 5 8h 11 = 5 5 5 8h 11 5 8h 11 = 5 8h 11 ( h 2)( 5 8h 11 ) = 8( 2 h ) ( h 2)( 5 = 8 2 5 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 = 8h 11 ) 4 5 = Answer: 14. lim x3 lim x3 4 5 7 3x 4 5 x 2 36 9 7 3x 4 5 x 2 36 9 16 4 = 81 9 0 0 = We need to rationalize both the numerator and the denominator in the fraction. Thus, lim x3 lim x3 lim x3 lim x3 lim x3 7 3x 4 5 x 2 36 9 7 3x 4 5 x 36 9 2 = 7 3x 4 7 3x 4 5 x 2 36 9 5 x 2 36 9 ( 7 3x 16 ) ( 5 x 2 36 9 ) ( 5 x 2 36 81) ( 7 3x 4 ) = ( 3x 9 ) ( 5 x 2 36 9 ) ( 5 x 2 45 ) ( 7 3x 4 ) = 3 ( x 3 ) ( 5 x 2 36 9 ) 5 ( x 2 9 ) ( 7 3x 4 ) = Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 3 ( x 3 ) ( 5 x 2 36 9 ) lim x3 lim 5 ( x 3 ) ( x 3 ) ( 7 3x 4 ) 3 ( 81 9 ) 3 ( 5 x 2 36 9 ) x3 = 3 (18 ) = = 5( 6) (8) = 5 ( 6 ) ( 16 4 ) 5 ( x 3 ) ( 7 3x 4 ) 1 ( 18 ) 3 (18 ) 1( 9 ) 9 = = = 5 ( 6 ) ( 8 ) 5 ( 2 ) ( 8 ) 5 (1 ) ( 8 ) 40 15. lim h0 16 x 16h 25 h Answer: 9 40 16 x 25 COMMENT: We will need to calculate this limit in order to find the derivative of the function y 16 x 25 using the definition of derivative. lim 16 x 16h 25 h 16 x 25 lim 16 x 16h 25 h 16 x 25 lim 16 x 16h 25 h 16 x 25 h0 h0 h0 lim h0 lim h0 16 x 25 0 = 0 0 16 x 16h 25 16 x 25 16 x 16h 25 16 x 25 16 x 25 ) = 16 x 25 ) = 16h h ( 16 x 16h 25 = = 16 x 16h 25 (16 x 25 ) h ( 16 x 16h 25 16 x 25 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 = lim h0 16 16 x 16h 25 16 2 16 x 25 16. 16 16 x 25 = 16 x 25 16 x 25 8 = 16 x 25 = 8 Answer: 16 x 25 ( x h )3 x3 lim h0 h COMMENT: We will need to calculate this limit in order to find the 3 derivative of the function y x using the definition of derivative. We will use the Binomial Expansion theorem in order to find the four terms 3 in the expansion of ( x h ) . Binomial Expansion Theorem Let n be a positive integer. Let a and b be n n n k k n n! n ( a b ) a b real numbers, then , where k k k !( n k ) ! . k 0 Thus, by the Binomial Expansion theorem, we have that ( x h ) 3 x 3 3x 2 h 3xh2 h 3 ( x h )3 x3 x 3 3x 2 h 3xh2 h 3 x 3 lim = hlim = h0 0 h h 3x 2 h 3xh2 h 3 h ( 3x 2 3xh h 2 ) lim = hlim = h0 0 h h lim ( 3x 2 3xh h 2 ) = 3x 2 0 0 3x 2 h0 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 2 Answer: 3x 17. x 3 64 lim x4 x4 x 3 64 0 lim x4 x4 0 3 By the Factor Theorem, x 4 is a factor of x 64 . This factorization can be found using the factorization formula for the sum of cubes, which is a 3 b 3 ( a b ) ( a 2 ab b 2 ) 3 3 3 Since x 64 = x 4 , then replace all the a’s in the formula by x and replace the b’s in the formula by 4. Thus, we have that x 3 64 = x 3 43 = ( x 4 ) ( x 2 x4 4 2 ) = ( x 4 ) ( x 2 4 x 16 ) 3 The factorization of x 64 can also be found using synthetic division. 3 3 2 Since x 64 = x 0 x 0 x 64 , then we write the following in order to carry out the synthetic division 1 0 4 0 64 16 64 1 4 16 4 0 3 2 Thus, x 64 = ( x 4 ) ( x 4 x 16 ) . Thus, evaluating the given limit, we have that x 3 64 ( x 4 ) ( x 2 4 x 16 ) lim lim lim ( x 2 4 x 16 ) = = = x4 x4 x4 x4 x4 16 16 16 3 (16 ) 48 Answer: 48 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 18. 8t 3 27 lim 3 2t 3 t 2 8t 3 27 0 lim 3 2t 3 0 t 2 3 By the Factor Theorem, 2t 3 is a factor of 8t 27 . This factorization can be found using the factorization formula for the difference of cubes, which is a 3 b 3 ( a b ) ( a 2 ab b 2 ) 3 3 3 Since 8t 27 = ( 2t ) 3 , then replace all the a’s in the formula by 2t and replace the b’s in the formula by 3. Thus, we have that 8t 3 27 = ( 2t ) 3 33 = ( 2t 3 ) ( ( 2t ) 2 ( 2t ) 3 32 ) = ( 2t 3 ) ( 4t 2 6t 9 ) 3 The factorization of 8t 27 can also be found using synthetic division. 3 3 2 Since 8t 27 = 8t 0t 0t 27 , then we write the following in order to carry out the synthetic division 8 0 12 0 27 18 27 8 12 18 3 2 0 3 2 3 t ( 8t 12t 18 ) . Factoring out the 2 that is 8 t 27 Thus, = 2 2 common to all terms in the second factor of 8t 12t 18 , we obtain that 3 2 3 2 8t 3 27 = t ( 8t 12t 18 ) = t 2 ( 4t 6t 9 ) . Now, 2 2 3 distributing the 2 through the first factor of t , we obtain that 2 Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 8t 3 27 = ( 2t 3 ) ( 4t 2 6t 9 ) . Thus, evaluating the given limit, we have that 8t 3 27 ( 2t 3 ) ( 4t 2 6t 9 ) lim lim lim ( 4t 2 6t 9 ) = = = 3 3 3 2t 3 2t 3 t t t 2 2 2 9 9 9 3 ( 9 ) 27 Answer: 27 f ( x ) L and lim g ( x ) M , and c Theorem (Properties of Limits) If xlim a xa is any real number, which will called a constant, then 1. 2. 3. 4. 5. 6. lim c c xa lim c f ( x ) = c lim f ( x ) c L xa xa lim [ f ( x ) g ( x ) ] = lim f ( x ) + lim g ( x ) L M xa xa xa lim [ f ( x ) g ( x ) ] = lim f ( x ) lim g ( x ) L M xa xa xa lim [ f ( x ) g ( x ) ] = lim f ( x ) lim g ( x ) L M x a x a xa lim f ( x ) L f ( x) xa lim M 0 = x a g( x ) lim g ( x ) M , provided that xa 7. lim x n a n provided that a n is defined xa Proof: These properties are proved using the formal definition of limit. Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850 x 4 6x3 7 Example Find xlim using properties of limits. 2 3x 2 x 5 x 6x 7 = 3x 2 x 5 4 lim x2 3 lim ( x 4 6 x 3 7 ) x2 lim ( 3x x 5 ) = 2 x2 lim x 4 lim 6 x 3 lim 7 x2 x2 x2 lim 3x lim x lim 5 = 2 x2 x2 x2 lim x 4 6 lim x 3 lim 7 16 48 7 24 6 ( 2 )3 7 57 2 = = = 2 3 lim x lim x lim 5 12 2 5 3( 2 ) 2 5 15 x2 x2 x2 x2 x2 x2 f ( x) f ( x ) 0 and lim g ( x ) 0 , then xlim Theorem If xlim a g ( x ) does not exist a xa (DNE). f ( x) f ( x) lim L . Then Proof: Suppose that xlim does exist, say that a g( x ) x a g( x ) f ( x) f ( x) lim g ( x ) = lim g ( x) = L 0 0. xlim xa x a a g( x ) g( x ) f ( x) lim lim f ( x ) 0 This is a contradiction to the fact that x a . Thus, x a g ( x ) does not exist. lim f ( x ) = xa NOTE: This type of proof in mathematics is called a proof by contradiction. In a proof by contradiction, an assumption is made and is used along with other information to obtain a conclusion that contradicts known information. The assumption, which is made, is usually the opposite of what you want to prove. Copyrighted by James D. Anderson, The University of Toledo www.math.utoledo.edu/~anderson/1850